Assessing Seafloor Litter Classification: Lessons from an Online Proficiency Test - Eirin Husabø; Briony Silburn; Thomas Maes; Lisa I. Devriese; Francois Galgani; Ulrike Kammann; Noreen E. Kelly; Christopher Kim Pham; Stephanie Lavelle; Fiona Preston-Whyte; Josie Russell; Katja Norén; et al. (Environmental Management, 2026)

Setting the course: aligning European Union marine pollution policy ambitions with environmental realities - Lisa I. Devriese; Thomas J. Verleye; Thomais Vlachogianni; Thomas Maes; Ben Boteler; Linda Del Savio; Andy M. Booth; Kathrin Kopke (Frontiers in Marine Science, 2025)
Pollution in coastal and marine waters is a global challenge that transcends national boundaries, affecting interconnected seas, the ocean and broader ecosystems. Addressing marine pollution requires policies that encompass not only the marine domain but the entire ecosystem, including human societies. Therefore, a comprehensive and integrated governance approach, linking land-based sources to marine environments, is essential for effective pollution management and mitigation. This study assesses the current environmental status of persistent, long-lasting and emerging pollutants (PCBs, excess nutrients, microplastics, PFAS, and underwater noise) and cumulative effects of pollution, and compares these with the set European Union (EU) environmental goals and ambitions. A systematic review of EU policy documents reveals that several targets are unclear, arbitrary, and often unattainable, limiting the effectiveness of current strategies. This paper presents five actionable recommendations to strengthen marine environmental policy, emphasizing the need for better alignment between EU ambitions and environmental realities. To enhance EU pollution policies, it is crucial to reinforce regulatory frameworks, ensure the effective enforcement of existing legislation, foster collaboration across sectors, and empower citizens and NGOs. Additionally, integrating health and pollution policies, ensuring public access to pollution data and knowledge, and establishing international leadership in pollution efforts are key for making informed decisions and achieving ambitious pollution reduction targets.

Corrigendum to “Evaluation of historic and new detection algorithms for different types of plastics over land and water from hyperspectral data and imagery” [Remote Sensing of Environemnt 298 (2023) 113834] - Alexandre Castagna; Heidi M. Dierssen; Lisa I. Devriese; Gert Everaert; Els Knaeps; Sindy Sterckx (Remote Sensing of Environment, 2024)

Evaluation of historic and new detection algorithms for different types of plastics over land and water from hyperspectral data and imagery - Alexandre Castagna; Heidi M. Dierssen; Lisa I. Devriese; Gert Everaert; Els Knaeps; Sindy Sterckx (Remote Sensing of Environment, 2023)

A recipe for plastic: Expert insights on plastic additives in the marine environment - Thomas Maes; Fiona Preston-Whyte; Stephanie Lavelle; Alessio Gomiero; Andy M. Booth; Maria Jesus Belzunce-Segarra; Juan Bellas; Steven Brooks; Adil Bakir; Lisa I. Devriese; Christopher Kim Pham; Bavo De Witte (Marine Pollution Bulletin, 2023)

Distribution and sources of macrolitter on the seafloor in Belgian fisheries areas - David Vanavermaete; Katrien Verlé; Lisa I. Devriese; Karien De Cauwer; Coline De Schrijver; Els Torreele; Loes Vandecasteele; Milica Velimirovic; Kristof Tirez; Kris Hostens; Bavo De Witte (Frontiers in Marine Science, 2023)
Marine litter is recognized as a global environmental concern. Seafloor litter can provide important information to help assess the status of the marine ecosystem and is relatively easy to collect on a regular basis. The Belgian fisheries area covers different parts of the OSPAR Greater North Sea region and the Celtic Seas. In these regions, seafloor litter data were gathered by quantifying the litter items caught in the trawl net during two different fisheries surveys to investigate litter distribution on both regional and local scales. In the international beam trawl survey (BTS), covering essentially the OSPAR Greater North Sea and Celtic Seas, an average of 2.2 ± 0.05 items.ha -1 were caught with a median of 1.4 items.ha -1 . In the environmental monitoring survey (EMS) only the Belgian part of the North Sea was covered and a smaller cod-end mesh size was used, resulting in 12.7 ± 1.7 litter items.ha -1 in the coastal zone (< 12 nm) and 2.8 ± 0.2 items.ha -1 in the more offshore zone (> 12 nm). In both surveys plastic items were predominant, representing up to 88% of the collected litter in the Belgian part of the North Sea. The impact of human activities at sea such as fisheries, sand extraction, wind farms and dredge disposal was investigated. A significant correlation was found between fishing activities and the amount of litter registered in the Belgian part of the North Sea, but not for the OSPAR Greater North Sea and Celtic Seas.

Fish out of water: consumers’ unfamiliarity with the appearance of commercial fish species - Marine Cusa; Luara Falcão; Joseph De Jesus; Cristina Biolatti; Lancelot Blondeel; Fiona S. A. Bracken; Lisa Devriese; Sandra Garcés-Pastor; Styliani Minoudi; Chrysoula Gubili; Pier Luigi Acutis; Stefano Mariani (Sustainability Science, 2021)
Seafood labels play an increasingly key role in assisting consumers in purchasing processed and featureless fish products, and in encouraging sustainable fishing and aquaculture practices. While informed purchasing choices are typically influenced by traceability and labelling awareness, they also depend on the consumers’ ability to identify and discriminate the fish species available on the market, which to date remains notably unexplored. We asked 720 people across six European countries to identify pictures of six fish species commonly sold in Europe. We reveal that European consumers have a poor understanding of the appearance of the fish they consume (overall ∼ 30% correct identification), with British consumers performing the poorest and Spanish ones doing best. We noted cultural association with some species, whereby the most regionally consumed fish are more easily recognized. We argue that despite recent improvements in technological solutions, stakeholder dialogue, and policy implementation, seafood market transparency will remain open to malpractice until consumers restore connection with their food.

Pinpointing the role of Aeromonas salmonicida in the development of skin ulcerations in common dab ( Limanda limanda ) - Maaike Vercauteren; Evelien De Swaef; Annelies Maria Declercq; Johan Aerts; Bart Ampe; Snorre Gulla; Freddy Haesebrouck; Lisa Devriese; Annemie Decostere; Koen Chiers (Journal of Fish Diseases, 2020)
Aeromonas salmonicida was isolated from ulcerations in common dab ( Limanda limanda ). An experiment was performed to pinpoint its role in ulceration development, considering the importance of the skin barrier and the pigmented and non‐pigmented sides. The skin of dab was treated in three zones, one where scales and epidermis were removed, one where mucus was discarded and one non‐treated zone. Fish were tagged to allow individual identification and challenged with A. salmonicida . Mortality and severity of the developing lesions were recorded for 21 days post‐inoculation. Starting 12 days post‐inoculation, mortality occurred gradually in challenged fish; however, no direct cause could be established. Both control fish and challenged fish developed ulcerations containing A. salmonicida. S equencing of vap A gene revealed that isolates retrieved from both groups were distinct, suggesting the presence of A. salmonicida prior to the trial. Most ulcerations developed in zones where skin was removed, suggesting that abrasion might be a predisposing factor in ulceration development. Ulcerations were also observed at the insertion site of the tag, where exposed muscle tissue might have favoured the development of ulcerations . In conclusion, A. salmonicida seems to be involved in the development of skin ulcerations in dab, although the exact pathogenesis needs to be elucidated.

Microplastics Baseline Surveys at the Water Surface and in Sediments of the North-East Atlantic - Thomas Maes; Myra D. Van der Meulen; Lisa I. Devriese; Heather A. Leslie; Arnaud Huvet; Laura Frère; Johan Robbens; A. Dick Vethaak (Frontiers in Marine Science, 2017)